PENGUSAHA MIKRO RENGGINANG DESA TEMPURSARI KECAMATAN DONOMULYO KABUPATEN MALANG - Priyo Sugiharto, Didik; Purwanto, Nanang (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2017)
One of the typical traditional snacks in Java is rangginang. This snack is made from sticky rice. There are two types of glutinous rice commonly used as raw materials rangginang, namely black and white rice sticky rice. There is no difference about the taste of the two ingredients. The most striking difference lies only in the color of its appearance that refers to the color of raw materials, ie black and white. The underlying goals for developing this business are (1) Want to lift the traditional food to the community, so as not to be displaced by the types of modern food. (2) To create business opportunities for Tempursari people in particular and Donomulyo District community in general. (3) To increase income so that people can fulfill their life needs thus it will be able to improve their welfare. (4) Creating rural economic growth so as to prevent migration from rural to urban. Problems faced by partners in terms of production are low productivity, product quality, capital and packing while in terms of management is related to financial bookkeeping, marketing knowledge and entrepreneurship. Solutions are given to solve problems faced by partners by providing rengginang printing production tools and tools for glutinous cooking to improve productivity and quality as well as training (entrepreneurship, marketing and bookkeeping).